Vzpostavljanje storitve EOD - "e-knjige po naročilu" v NUK - Svoljšak, Sonja (Knjižnica, 2010)
The article gives an insight into DOD project as a means for synergic solutions in the field of new library services establishment on the European level. It presents the activities and tasks completed within the project with an emphasis on three main project work packages: EOD service implementation, dissemination and communication and market analysis. A statistical overview of the EOD eBooks orders received by NUK from 2007 to 2009 is given and the results of market analysis are presented. The article concludes with an overview of current EOD network activities and some future projections.
Keywords: digitalizacija; digitization; e-knjige; uporabniki; storitve; evropski projekti